How VA Whole Health Coaching Can Impact Veterans' Health and Quality of Life: A Mixed-Methods Pilot Program Evaluation. (March 2021) - Purcell, Natalie; Zamora, Kara; Bertenthal, Daniel; Abadjian, Linda; Tighe, Jennifer; Seal, Karen H
Purpose: To examine the impact of a pilot VA Whole Health Coaching program, including whether and how the program helps veterans improve their health and quality of life. Intervention: Whole Health Coaching is a structured program to support veterans in making healthy behavior changes to promote holistic well-being. Design: This mixed-methods quality-improvement evaluation combined surveys (pre- and post-coaching) with follow-up qualitative interviews. Setting: The setting was a large VA healthcare system, encompassing a medical center and six community-based clinics in Northern California. Participants: 65 veterans completed surveys at both time points; 42 completed qualitative interviews. Method: Telephone surveys administered at baseline and 3 months assessed global health (PROMIS-10), perceived stress (PSS-4), and perceived health competency (PHCS-2). Pre- and post-scores were compared using t-tests. A subsample of participants completed a qualitative interview evaluating program experience, goal attainment, and the coaching relationship. Results: Surveys showed significant improvements over baseline in mental health (p = 0.006; d = 0.36), stress (p = 0.003; d = –0.38), and perceived health competence (p = 0.01; d = 0.35). Interviewees were highly satisfied with their coaching experience, describing both effective program components and improvement opportunities. Conclusion: Whole Health Coaching can help participants make meaningful progress toward health goals, reduce stress, and improve quality of life. The Whole Health model's emphasis on holistic self-assessment; patient-driven goal-setting; supportive, non-judgmental inquiry; and mindful awareness contributed to program success and enhanced participants' experience.